Factors influencing survival of female elk in a harvested population - Conard, Jonathan M.; Sandercock, Brett K.; Gipson, Philip S.; Ballard, Warren B. (My University, 2013)
Understanding the influence of management actions and environmental conditions on demographic vital rates is important for effective conservation and management of wildlife populations. We used radio-telemetry to monitor annual and seasonal survival of 34 female elk Cervus elaphus at Fort Riley, Kansas in a 3.5-y field study (November 2003 to February 2007). We modeled the relationship between individual and environmental covariates and survival rates of female elk. We observed eight mortalities, and harvest was the primary cause of mortality in our study population. Annual survival rates of female elk in Kansas (0.76) were similar to other harvested populations of elk. Among the candidate model set, models that included age as a covariate were most supported. Parameter estimates from top models provided support for a slight negative relationship between age and survival. Monthly survival estimates during hunting season declined with age from 0.98 for 1.5-y-old females to 0.80 for 16.5-y-old females.
Keywords: Cervus elaphus; Demography; Elk; Mortality; Survival